Pengaruh Brand Image dan Electronic Word Of Mouth Terhadap Purchase Intention (Studi Pada Konsumen Angkringan Pinarak Mojokerto) - Krisna Tiknanda Arman; Nur Hidayati; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This type of research is an explanatory research with a quantitative approach. This research was conducted in Angkringan Pinarak, Mojokerto. The population in this study is not known with certainty. The sampling technique used snowball sampling so that the sample in this study amounted to 90 respondents. The variables used in this study are brand image and electronic word of mouth as the dependent variable, purchase intention as the independent variable. For the measurement of these variables, which is used to measure the responses of respondents in this study using a Likert Scale by testing the validity and reliability tests first. Data analysis was carried out, namely descriptive statistical analysis analysis consisting of classical assumption test, multiple linear regression analysis, t test, F test and coefficient of determination using SPSS 25. This study finds that Brand image and Electronic word of mouth (eWOM) have a simultaneous effect on Purchase Intention at Angkringan Pinarak Mojokerto. Brand image has a partial effect on Purchase Intention at Angkringan Pinarak Mojokerto. Electronic word of mouth has a partial effect on purchase intention at Angkringan Pinarak Mojokerto. Keyword : Brand Image, Electronic Word Of Mouth, Purchase Intentiom.